2013
DOI: 10.1111/apm.12112
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic potential and genetic diversity of environmental and clinical isolates ofPseudomonas aeruginosa

Abstract: The aim of this study was to investigate the occurrence of virulence genes among clinical and environmental isolates of Pseudomonas aeruginosa and to establish their genetic relationships by Enterobacterial Repetitive Intergenic Consensus PCR (ERIC-PCR). A total of 60 P. aeruginosa isolates from environmental and clinical sources were studied. Of these, 20 bacterial isolates were from soil, 20 from water, and 20 from patients with cystic fibrosis. Analysis of ERIC-PCR demonstrated that the isolates of P. aerug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
(49 reference statements)
3
18
0
Order By: Relevance
“…The most common virulence genes were lasB and plcH , present in 76 and 74% of the isolates respectively. Similar results to the present study were found by Martins et al in a study of 60 P. aeruginosa isolates from clinical and environmental sources, showing that lasB and plcH genes were present in 80 and 58% of the isolates respectively. Moreover, with respect to these genes, Mitov et al , after investigating virulence genes in a collection of 202 clinical P. aeruginosa, also found a high frequency of lasB (100%) and plcH (92%) genes.…”
Section: Resultssupporting
confidence: 93%
“…The most common virulence genes were lasB and plcH , present in 76 and 74% of the isolates respectively. Similar results to the present study were found by Martins et al in a study of 60 P. aeruginosa isolates from clinical and environmental sources, showing that lasB and plcH genes were present in 80 and 58% of the isolates respectively. Moreover, with respect to these genes, Mitov et al , after investigating virulence genes in a collection of 202 clinical P. aeruginosa, also found a high frequency of lasB (100%) and plcH (92%) genes.…”
Section: Resultssupporting
confidence: 93%
“…This was studied for Burkholderia cepacia , Pseudomonas aeruginosa and Stenotrophomonas maltophilia (Ryan et al, 2009; Martins et al, 2013). Unfortunately, these plant-associated bacteria can infect immuno-compromised patients with high predisposition in hospitals.…”
Section: Indoor Microbiomes— Importance and Originmentioning
confidence: 99%
“…Genetic analysis of strains derived from diverse sources (human, animal and environmental) report a largely nonclonal population structure with frequent genetic recombination . There is extensive overlap in the genomes of strains isolated from environmental and human sources, and wild type environmental isolates express an extensive set of virulence genes that may promote pathogenicity to animals …”
Section: Introductionmentioning
confidence: 99%
“…6 There is extensive overlap in the genomes of strains isolated from environmental and human sources, 6,19 and wild type environmental isolates express an extensive set of virulence genes that may promote pathogenicity to animals. 20 The objectives of the observational study reported here were to survey a population of dogs with bacterial otitis externa using a case-control design, in order to assess various environmental and nosocomial exposures as potential risk factors for acquisition of P. aeruginosa. It was hypothesized that P. aeruginosa isolates derived from infected ears would be clonal to isolates derived from household water sources and the mouths of human and animal (dog and cat) companions of the study subjects.…”
Section: Introductionmentioning
confidence: 99%